Wholesale fruit trade in the Federal District: An exploratory analysis (Research, Society and Development, 2024)
The aim of this study was to analyze the fruit wholesale trade in the Federal District based on an exploratory survey of companies representing the sector. Specifically, it sought to identify the profile of the companies, explain the characteristics of the transactions, elucidate aspects of supply and learn about the challenges faced by the local fruit wholesale sector. The methodology used consisted of field research, using an online questionnaire and face-to-face interviews with business managers. The result was a significant number of medium-sized companies (with up to 100 employees) that have been in operation for more than ten years. These companies make contracts with rural producers and also contain production.  In addition, they supply various types of retail outlets (from street markets to hypermarkets), operate in five other states (MG, RJ, SP, BA, GO and TO) and sell up to 31 types of fruit, including bananas, papaya, apples and grapes. In conclusion, it can be said that the fruit wholesale sector in the Federal District plays a significant role in local and regional supply and is made up of solid, experienced companies that serve a broad regional and national market. They stand out for their longevity, capacity for self-supply, wide distribution and focus on product quality. However, entering and remaining in this market requires great efforts to bear the costs of equipment and transportation and storage logistics, as well as facing unfair competition, high taxes and a lack of government support for the sector.